Evaluation and Management of Septic Arthritis and its Mimics in the Emergency Department - Brit Long; Alex Koyfman; Michael Gottlieb (Western Journal of Emergency Medicine, 2019)
Septic arthritis is a dangerous medical condition associated with significant morbidity and mortality. However, the differential diagnosis can be broad with conditions that mimic this disease and require different evaluation and treatment. This narrative review presents the emergency medicine evaluation and management, as well as important medical conditions that may mimic this disease. Septic arthritis commonly presents with monoarticular joint pain with erythema, warmth, swelling, and pain on palpation and movement. Fever is present in many patients, though most are low grade. Blood testing and imaging may assist with the diagnosis, but the gold standard is joint aspiration. Management includes intravenous antibiotics and orthopedic surgery consult for operative management vs. serial aspirations. Clinicians should consider mimics, such as abscess, avascular necrosis, cellulitis, crystal-induced arthropathies, Lyme disease, malignancy, osteomyelitis, reactive arthritis, rheumatoid arthritis, and transient synovitis. While monoarticular arthritis can be due to septic arthritis, other medical and surgical conditions present similarly and require different management. It is essential for the emergency clinician to be aware how to diagnose and treat these mimics.